Coverage of Miller class I and II gingival recessions treated with subepithelial connective tissue graft, acellular dermal matrix, and enamel matrix proteins. Pilot study - ARONI,Mauricio Andrés Tinajero (2016)
Abstract Objective The aim of this study was to compare clinical findings obtained in the treatment of gingival recessions using subepithelial connective tissue graft (SECT), acellular dermal matrix (ADM), and enamel matrix proteins (EMP). Material and method Twelve patients with Miller class I and II recession in the canines or upper premolars were randomly divided into groups to receive treatments using SECT, ADM, or EMP. Clinical measurements were performed before and three months after surgical procedures. The data evaluated were as follows: percentage of root coverage, height and width of gingival recession, probe depth, clinical attachment level, and height and thickness of keratinized gingiva. The Kruskal-Wallis test complemented by Dunn’s test was used to perform the between-group, analysis and the Wilcoxon test was used to perform the within-groups analysis. The tests were applied at the 95% confidence level. Result The SECT and ADM groups had a higher percentage of root coverage and greater reduction in the height and width of gingival recessions compared to the EMP group (p<0.05). Conclusion The SECT and ADM are more effective in treating gingival recessions than EMP.